Sobre las sucesiones marinas del aptiano en cercanías de ortega y ataco (tolima - colombia) (2002)
It is studied the stratigraphy of the successions containing the lowest Cretaceous marine rocks along the Urapa (Olaya Herrera) and Los Huevos (Ataco) creeks into the Caballos Formation.  Overlying the Saldaña Formation lies a succession variable in thickness that starts with continental deposits, followed by transitional and open sea, and finishing with transitional deposits.  Into the marine rocks were identified Cheloniceras (Epicheloniceras) cf. pardoi ETAYO-SERNA, Ch. (E.) cf. bambucaense ETAYO-SERNA, Roloboceras cf. saxbyi CASEY, bivalvs and gastropods. In the whole, this asemblage represents middle to late Aptian.